Rules of Evidence: A Comparative Study of Al-Majallah al-Aḥkām al-Adaliyyah (1876) and Indian Evidence Act (1872) (Al-Qamar, 2025)
This paper analyzes the rules of evidence as articulated in Indian Evidence Act (IEA) 1872 and the Ottoman Civil Code known as Al-Majallah al-Aḥkām al-Adaliyyah (Majallah). Both laws were enacted in the same era, i.e., 1870s, and have enjoyed a considerable influence. Their spatial proximity makes a case for their content analysis in a comparative manner. They have evolved similar rules in some areas, while differed on others. They are averse to hearsay evidence, and allow it occasionally. They follow comparable rules in the domains of admissions and presumptions. They recognize the concept of documentary evidence. Both laws are founded considerably differently in some important respects, such as, competency of witnesses, number of witnesses, and relevancy of facts and reliability of evidence. While specific number as well as gender of witnesses is pre-requisite for proving civil cases in the Majallah, the IEA emphasizes on quality of evidence instead of quantity and gender of witnesses. The administration of oath to the parties is one of the grounds for decision under the Majallah, but it is conspicuously absent from the IEA. Despite introductory nature of this study, the paper enriches academically about the considerations and thoughts shaping two great legal traditions, i.e., Islamic law and common law, for discovery of truth in litigious matters.
Keywords: Evidence; rules; Majallah; Indian Evidence Act